Comparative studies on the purification process of bioethanol from rice husks - Siti Aishah, Mustafa (2006)
The objective of this research is to study the purification process of bio-ethanol production by different distillation methods. In this research, continuous study is done which the same production method is repeated, scaled up and improved. After production process, the process is continued with the comparative studies on the purification process.In the previous thesis, rice husks is selected as the raw material for the production of bio-ethanol from biomass waste. The production method comes into 3 main processes which are the pre-treatment of rice husks using NaOH at ambient condition, followed by enzymatic hydrolysis , and end up with anaerobic fermentation After bio-ethanol is produced, simple distillation is done first for the on the purification followed by the extractive distillation which used ethylene glycol as solvent. Then, the effect of adding salt in ethylene glycol is determined by performing extractive distillation with salt. The distillation processes are compared. It is proven that by scaling up the anaerobic fermentation process yields higher amount of bio-ethanol which is 8.3 vol% and 6.3 wt% in weight composition than in the previous thesis. The extractive distillation with salt performed the highest result in concentrating the bio-ethanol to 22 vol% and 17 wt% in weight composition. As a conclusion, purification process by the extractive distillation with salt yields the highest performance in removing water from bio-ethanol and better than other distillation process.